ARTI PENTINGNYA KETERANGAN DPR DAN PRESIDEN DALAM PROSES UJI MATERI UNDANG-UNDANG - Retno Mawarini Sukmariningsih (Jurnal Dinamika Hukum, 2013)
In judicial review, the applicant is Indonesian citizen or legal person in legal standing. The parliament and president could be present in the court. The parliament and president statement needs in judicial review. Because they know about the philosophy of legislation making process. This fact is the reflection of justice in the Constitutional Court decision, legal certainly, and benefit for all parties. The consequence of decision of the constitutional court is: to execute the decision of the constitutional court that binds force legally. The obligation parliament showed on the verdict. Whether accepted or rejected influences to the revision of legislation, based on the constitution of 1945 RI, the parliament and president oblige to revise legislation, in fact the constitutional court had the conditional verdict to declare its decision and to legalize in Indonesian gazette as legal fiction.Keywords   : judicial review, legal standing, ex nune, lex imperpecta.